2022
DOI: 10.3390/insects13030300
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of CYP6 Family Genes from the Oriental Fruit Moth (Grapholita molesta) and Their Responses to Insecticides

Abstract: Cytochrome P450 (CYP) monooxygenases comprise a superfamily of proteins that detoxify xenobiotics and plant secondary metabolites in insects. The CYP6 family is unique to the class Insecta, and its members participate in the metabolism of exogenous substances. In this study, we sequenced and characterized the full-length cDNAs of eight CYP6 family genes from Grapholita molesta (Busck), a global pest of pome fruits. P450 genes with the exception of CYP6AN35, which was most highly expressed in adults, consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…In addition to investigating the structures of P450s, the overexpression of P450s, especially those of the CYP3 and 4 clades, has been explored, and the results indicated that these enzymes are related to insecticide resistance or tolerance. For example, the expression levels of AgCYP6CY7, AgCYP6CY21, AgCYP4CJ1, and AgCYP380C6 in a cyantraniliprole-resistant A. gossypii strain, 45 GmCYP6AB112 and GmCYP6AB113 of Grapholita molesta, 46 and PxCYP6BG1 of Plutella xylostella 47 were increased in response to diamide treatments. Moreover, upregulated P450 expression levels were found to be associated with plant allelochemical exposure.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to investigating the structures of P450s, the overexpression of P450s, especially those of the CYP3 and 4 clades, has been explored, and the results indicated that these enzymes are related to insecticide resistance or tolerance. For example, the expression levels of AgCYP6CY7, AgCYP6CY21, AgCYP4CJ1, and AgCYP380C6 in a cyantraniliprole-resistant A. gossypii strain, 45 GmCYP6AB112 and GmCYP6AB113 of Grapholita molesta, 46 and PxCYP6BG1 of Plutella xylostella 47 were increased in response to diamide treatments. Moreover, upregulated P450 expression levels were found to be associated with plant allelochemical exposure.…”
Section: ■ Discussionmentioning
confidence: 99%
“…For example, the expression levels of AgCYP6CY7 , AgCYP6CY21 , AgCYP4CJ1, and AgCYP380C6 in a cyantraniliprole-resistant A. gossypii strain, GmCYP6AB112 and GmCYP6AB113 of Grapholita molesta , and PxCYP6BG1 of Plutella xylostella were increased in response to diamide treatments. Moreover, upregulated P450 expression levels were found to be associated with plant allelochemical exposure. ,, DaCYP6CR2 and DaCYP6DE5 expression in D.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the P450 genes related to insecticide resistance are mainly concentrated in the CYP3 (including CYP6 and CYP9) and CYP4 families ( Feyereisen, 2012 ). In this study, the MusiDN2722 sequence cloned from M. usitatus was used to construct a phylogenetic tree and was found to belong to the CYP6 clade, the family members of which have also been shown to play important roles in the detoxification and metabolism of toxic substances ( Pan et al, 2018 ; Han et al, 2022 ). Through comparison with CYP genes of the same family in other insects, it was found that MusiDN2722 shared the characteristic CYP450 sequence with other model insects, containing highly conserved hydrogen-bonding regions, including Helix-C (WxxxR), Helix-I (AGxxT), Helix-K (ExxR), Meander (FxxGxRxxxG), and the heme-binding domain (PxxFxPxxF) ( Feyereisen, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…melanogaster dietary exposure to permethrin and cyp4e3 knockdown caused a significant elevation of oxidative stress-associated markers in the Malpighian tubules, which included lipid peroxidation based on the production of 4-hydroxynonenal; these findings have increased our understanding of the molecular mechanisms of permethrin detoxification in the Malpighian tubules [ 36 ]. These observations indicate that the fat body, midgut, and Malpighian tubules are essential tissues for detoxification [ 37 , 38 ]. In particular, the expression of Pocyp4d2 was higher in the midgut than in other tissues.…”
Section: Discussionmentioning
confidence: 99%